Neothalassius, a new genus of Parathalassiinae (Diptera: Dolichopodidae s.lat.) from the Pacific coast of South America - Brooks, Scott E.; Cumming, Jeffrey M. (Zootaxa, 2016)
A new genus, Neothalassius gen. nov., and two new species, Neothalassius triton sp. nov. and Neothalassius villosus sp. nov., are described from rocky shorelines along the Pacific seacoast of South America. The phylogenetic placement of Neothalassius within the subfamily Parathalassiinae is discussed.